2009
DOI: 10.4049/jimmunol.0901154
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Increase in the Ratio between Foxp3+ and IL-17-Producing CD4+ T Cells in Healthy Pregnancy but Not in Preeclampsia

Abstract: Preeclampsia is the leading cause of morbidity and mortality in pregnancy. Although the etiology of preeclampsia is still unclear, it is believed to involve rejection of the fetus, possibly due to an imbalance between regulatory (Treg) and effector T cells. To test this, we compared the frequencies of circulating CD4+ T cells expressing Foxp3, IFN-γ, IL-10, or IL-17 at the end of the third trimester of healthy and preeclamptic pregnancies. The size of the Treg cell compartment, defined by the frequency of CD4+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
344
7
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(378 citation statements)
references
References 44 publications
25
344
7
2
Order By: Relevance
“…31,32 In our study, the frequency of Th17 cells to CD4 + T cells during all stages of pregnancy period was similar to that in non-pregnant women, 32 but Santner-Nanan et al 33 reported that the frequency of Th17 cells in the third trimester of pregnancy was significantly lower compared to that of non-pregnant women. Further studies are needed to determine circulating Th17 cell levels during pregnancy.…”
Section: Th1/th2/th17 and Treg Paradigms In Normal Pregnancymentioning
confidence: 65%
See 2 more Smart Citations
“…31,32 In our study, the frequency of Th17 cells to CD4 + T cells during all stages of pregnancy period was similar to that in non-pregnant women, 32 but Santner-Nanan et al 33 reported that the frequency of Th17 cells in the third trimester of pregnancy was significantly lower compared to that of non-pregnant women. Further studies are needed to determine circulating Th17 cell levels during pregnancy.…”
Section: Th1/th2/th17 and Treg Paradigms In Normal Pregnancymentioning
confidence: 65%
“…34 Previous studies demonstrate that elevation of IL-17 is observed in acute renal rejection, 35 suggesting that increased Th17 cells in pregnancy decidua might be disadvantageous for the maintenance of pregnancy. 33 Unexpectedly, the frequency of Th17 cells in the decidua is significantly higher compared to that in peripheral blood. The uterine cavity is not completely sterile, and therefore, Th17 cells might play a role to induce protective immune response against extracellular microbes.…”
Section: Th1/th2/th17 and Treg Paradigms In Normal Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, during pregnancy, Th1-type immunity is well controlled to avoid its overstimulation, probably due to the suppression by Treg, which are observed to increase in decidua (11). Furthermore, the level of IL-17 in normal pregnancy is lower than that in non-pregnancy, and Th17 is thought to be inhibited in the former condition (12). Taken together, in pregnancy, Th2/Treg-type immunity should be predominant over Th1/Th17-type immunity by the above changes in the hormones and cytokines, and the subsequent rebound of Th1/Th17 may occur after delivery.…”
Section: Discussionmentioning
confidence: 98%
“…In normal pregnancy, T reg cells prevent generation of an immune response against fetal tissue and a decrease in the number of T reg cells is associated with abortion (Saito et al, 2005). In contrast, T H 17 cells promote inflammation and increased levels of T H 17 cells -accompanied by a decrease in T reg cell levels -were reported to occur in association with unexplained RSA events (Santner-Nanan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%